Service Quality in Type 2 Diabetes from the Patients\' Perspective - Jafar sadegh tabrizi; saeide alidoost; amir bahrami; mohamad asghari jafarabadi (Tehran University of Medical Sciences, 2015)
Background: Given the importance of quality in health care and meeting the needs of patients, it seems important to measure the quality of services and identify the weaknesses from the patients' perspective. The purpose of this study is to assess the service quality (SQ) of care as perceived by people with Type 2 Diabetes (T2D). Materials & Methods: A cross-sectional study was conducted among 180 people with Type 2 diabetes in diabetes clinic using convenience sampling method in Tabriz, Iran in 2012. Service quality was calculated using: SQ=10 - (Importance ×Performance) based on importance and performance of non-health aspects from the patients' perspective. Validity and reliability of questionnaire was reviewed and confirmed. Independent sample T-test and ANOVA were used to investigate relationship between service quality and categorical variables. Data analyzed bySPSS13 software. Results: The average service quality score was 8.17 of 10. From the participants' perspective, of 12 aspects of service quality, communication and prevention had the highest score for importance. Dignity had the highest score for performance. However, the highest service quality values were for continuity of care, dignity and confidentiality. Conclusion: overall service quality achieved inadequate quality and there is an opportunity to improve quality of care.